“Winning Through Nutrition: The Ultimate Athlete's Guide to Sports Diet and Performance Enhancement” (International Journal of Food and Nutritional Sciences, 2021)
In the realm of sports nutrition, an athlete's dietary regimen can be influenced by a multitude of internal and external factors, all of which can impact the symptoms stemming from exercise-induced food allergies. This study's primary aim was to spotlight the diverse factors that directly shape athletes' dietary decisions. While these choices are pivotal for sustaining a healthy athlete, their efficacy hinges on variables such as timing, location, and the surrounding environment. As a result, it is strongly recommended that athletes heed the counsel of healthcare professionals and nutrition experts before embarking on training and competitive endeavors. Comprehending and scrutinizing the nutritional strategies and trends embraced by athletes before training sessions and competitions is of paramount significance. Further clinical trials may be imperative to pinpoint specific foods that athletes can incorporate into their diets to minimize adverse symptoms and enhance the outcomes of their training. The study's findings have led to a conclusive deduction.